Using Biochar and Coal as the Electrode Material for Supercapacitor Applications - Ding, Yan; Wang, Tao; Dong, Duo; Zhang, Yongsheng (Frontiers in Energy Research, 2020)
Millet straw activated carbon (MAC) and anthracite coal activated carbon(AAC) was prepared by thermal modification with a mass ratio of 5:1 (KOH:C) for supercapacitor (SC). The BET specific surface area of MAC and AAC is 1264.8 m2/g and 1695.1 m2/g with the average pore size of 3.018 and 2.170 nm, respectively. In the cyclic voltammetry test, the area of CVs of MAC electrode is obviously larger than that of AAC, especially at 100 mV/s and 200 mV/s. The ESR (0.28Ω) of AAC electrode is more than 6.5 times that of MAC electrode (0.043Ω) in the EIS test. In the GCD test, the results illustrate each specific capacitance of the activated biochar electrode is larger than AAC electrode. At the current density of 0.2 A/g, the specific capacitance of MAC electrode is 144 F/g, while the AAC electrode is only 85.2 F/g. The MAC electrode also presents a stable cycling performance with 125% after 10,000 cycles at 0.5A/g which is 11% higher than 114% of AAC and remains 99.5% and 97.4% of coulombic efficiency because of MAC’s rich tube structures and fish-scale-like inner surface. These encouraging results all indicate that excellent electrode material for supercapacitors can be obtained by activating cheaper millet straw biochar.